Characterization of Humic Acids Isolated from Selected Soils of Livingston Island by CP/MAS 13C NMR and ESR Spectroscopy - Evgeny Abakumov; Rositsa Yaneva; Vyacheslav Polyakov; Miglena Zhiyanski (Applied and Environmental Soil Science, 2022)
The tundra and tundra barrens of the maritime Antarctica represent a unique type of terrestrial ecosystem, geographically confined to the region of the Antarctic Peninsula and a number of surrounding archipelagos. Antarctic soils are underestimated in the quantity of organic matter (OM) pools, organic remnant humification/mineralization rates, and biogenic-abiogenic interactions. The structure of reserves for humic substances within the permafrost zone, as well as the role of the molecular composition of organic substances, are still poorly understood. In this study, we investigate humic acids of selected sub-Antarctic soils in terms of elemental and structural composition to evaluate OM stabilization degree and to assess carbon distributions in the molecules by solid-state CP/MAS 13C NMR and ESR spectroscopy. The results obtained show that the studied humic acids consist mainly of aliphatic structural fragments. According to ESR spectroscopy, it was noted that the most stable molecules by the data of ESR spectroscopy are formed in postornithogenic soils. In contrast, the average portion of the aromatic compounds is about 30% in humic acids, extracted from soils with evident ornithogenic effect.